… en la oscuridad y así con velas, con mecheros, se organizaban - Amandina Quispe; Vicente Romero (Les Cahiers ALHIM)
Amandina Quispe summarizes in this interview her social and cultural origin, her learning in the course of the fights of the Quechua’s people from Anta. She relates also upon her relations with the left-wing organizations. She tells us about her experiences and livings being a woman leader of the Confederación Campesina del Perú (CCP).